On Asian Transnational Adoptees’ Self-Determination for Cultural Identification: An Analysis of Greg Leitich Smith’s Novel, Ninjas, Piranhas, and Galileo (Journal of Advanced Research in Social Sciences, 2022)
Transnational adoption from Asian countries to the US started in the 1950s. When Asian transnational adoptees first came to the US, they were encouraged to assimilate into white American cultures because many were adopted by white Americans, yet due to the spread of the ideal of incorporating adoptees’ ethnic background in parenting for the adoptees’ healthy identity development in the US, white parents have started encouraging their adopted children to know their Asian cultural roots. While white parents are trying to give their adopted children either American culture or Asian culture, what do Asian adoptees feel about their cultural identification? Isn’t it Asian adoptees themselves who need to decide their cultural identification? This article examines these questions by reading Greg Leitich Smith’s Ninjas, Piranhas, and Galileo from interdisciplinary perspectives. Combining the literary texts and the findings of adoption research in the fields of anthropology, sociology, and psychology, this article concludes that while white adoptive parents need to provide cultural experiences of their adopted children’s birth culture to their children, it is Asian transnational adoptees themselves who have the right to decide their cultural identification.